A novel fuzzy vault scheme based on the feature level fusion of fingerprint and face features - Xun LI; Lin YOU; Jiahao LIANG; Chunhui YAN (Dianxin kexue)
Aiming at the problem that the biometric feature-based fuzzy vault is vulnerable to correlation attack and the loss of key and biometric template,and the authentication performance of fuzzy vault based on single biometric feature is unreliable,a novel fuzzy vault scheme based on the feature level fusion of fingerprint and face features was proposed.This scheme carried out irreversible transformation of fingerprint features and face features,and based on the Diffie-Hellman algorithm,the transformed fingerprints and face features were fused into a template at the feature level.Finally,the fusion template was used to construct the fuzzy vault.By updating the random matrix,the vault could be revoked,which could effectively resist the correlation attacks and achieve reliable authentication.Experimental results show that the proposed scheme improves the reliability of the system and the security of multiple biometric templates.